Fatores da qualidade de vida no trabalho intervenientes na transição para aposentadoria - Grudzinski, Silvia Cristina (2013)
The population growth of the elderly population is increasing more and more in Brazil and in several countries worldwide. Consequently businesses will be one of the sectors most affected by this growth in Brazil, since they will have to replace or keep these employees working for a few more years. This fact coupled with good programs Quality of Work Life (QWL) and Motivating Potencial Score can be a positive outlook to keep this worker on the job market for a few more years. In this context, the primary objective of this study was to measure among the eight criteria stipulated by Walton's QWL, which can interfere in the decision of elderly workers to remain working after retirement. The methodological approach consisted of a content analysis and a descriptive exploratory. Data analysis was based on descriptive statistics and quantitative research. The results from the proposed notes made in relation to the Human Resource (HR) will enable managers to have an overview of the level of understanding and commitment of older people in a business context. The conclusion indicates that 72.22% of elderly workers who are in the process of retirement plan to continue working after their retirement, to feel more active, independent and useful in society. However, the factor's QWL mentioned that they should be improved to make them feel safer and encouraged to work with more pleasure, would be the appropriate return, which would bring more peace and greater future professional and personal fulfillment. However, it is important that companies start to reflect on the training and retraining to enhance the employability of older workers allowing its replacement or stay in the labor market for some years.